Effects of particle morphology and magnetocrystalline anisotropy on < 111 > orientation and magnetostriction of sintered Tb-Dy-Fe/DyCu compacts. (August 2022) - Zhou, Zhiguang; Li, Jiheng; Bao, Xiaoqian; Liu, Miao; Yang, Zijing; Han, Zhaopeng; Gao, Xuexu
Abstract: Sintered Tb-Dy-Fe materials prepared by the compression molding method have higher relative density and energy density than powder-bonded composites. However, due to the low magnetocrystalline anisotropy and the cubic symmetry of the Laves structure, the orientation degree of sintered materials is relatively low and not beneficial for obtaining large magnetostriction. We prepared the sintered Tb-Dy-Fe/DyCu compacts with preferred <111 > orientation by applying magnetically oriented powder metallurgy. The dependence of orientation degree and magnetostriction of oriented Tb-Dy-Fe/DyCu sintered compacts on different particle morphology and Tb/Dy ratios were studied. The oriented Tb-Dy-Fe/DyCu sintered compacts prepared from the milled single crystal Tb-Dy-Fe powders gained a higher <111 > orientation due to the small rotational resistance when magnetic particles move in a magnetic field, achieving improved magnetostriction. Magnetocrystalline anisotropy which determines the rotational torque caused by the magnetic field is one of the important factors affecting the rotation behavior of magnetic particles in a magnetic field. We designed Tb-Dy-Fe alloys with different Tb/Dy ratios which have different magnetocrystalline anisotropy, and prepared the sintered Tb-Dy-Fe/DyCu compacts under the same process parameters. The magnetocrystalline anisotropy constant K1 of Tbx Dy1-x Fe1.95 (x = 0.27, 0.30, 0.33, 0.50) alloys increased from 0.66 × 10 6 J/m 3 to 3.85 × 10 6 J/m 3 by raising the Tb/Dy ratios, and the <111 > orientation degree of sintered Tb-Dy-Fe/DyCu compacts was promoted simultaneously. The oriented Tb0.33 Dy0.67 Fe1.95 /DyCu sintered compact achieved the highest <111 > orientation degree of 56.6%, resulting in the largest magnetostriction of 1326 ppm and the d 33 peak value of 6.81 nm/A. Graphical abstract: Image 1 Highlights: The near-spherical Tb-Dy-Fe particles improve the <111> orientation degree. The <111> orientation degree promoted by raising Tb/Dy ratios of Tb-Dy-Fe alloys. The higher <111> orientation degree resulted in higher magnetostriction. The low-field magnetostrictive performance was attributed to moderate K1 value.